"Solutions in Search of a Problem": Commentary on Videira and Rosa (2017) - Savage, Patrick E. (Empirical Musicology Review, 2018)
This commentary offers a review of Videira and Rosa's attempt to construct and validate an online corpus of fado transcriptions. While I support their application of music information retrieval (MIR) tools to diverse musical repertoires, I fear that a lack of clarity in their goals leads them to fall into the trap of finding "solutions in search of a problem" that is common in computational ethnomusicology. I highlight ways in which I believe they could improve future work on this project, including: 1) more interdisciplinary collaboration, 2) more clarity in their goals, and 3) the use of corpora and tools that are more suitable for comparing the symbolic data contained in their database of musical transcriptions.